Freshwater influx, hydrographic reorganisation and the dispersal of ice rafted detritus in the sub-polar North Atlantic Ocean during the last deglaciation - Small, D.; Austin, W.; Rinterknecht, V. (Journal of Quaternary Science, 2013)
A sediment core from the north-east North Atlantic contains high-resolution co-registered foraminiferal δ18O and ice-rafted detritus (IRD) records for the last deglaciation. These reveal a distinct ice-rafting event that occurred at the time of Greenland Interstade 1d (GI-1d), a feature also seen in other high-resolution cores from the North Atlantic. The occurrence of a geographically widespread peak in IRD at ice distal sites at a time when increased freshwater flux to the surface ocean is inferred to have caused rapid cooling suggests a mechanistic link between the processes, analogous to the Younger Dryas (GS-1) cooling episode. The general absence of IRD at southern locations at other times during GI-1 when the flux of icebergs from surviving ice sheets to northern locations continued suggests that the GI-1d IRD peak represents a time of hyrdrographic reorganization which changed IRD dispersal. While numerous studies have suggested freshwater flux as a major driver of rapid climate oscillations observed around the North Atlantic during the last deglaciation, the evidence presented here both supports that mechanism and highlights the potential for rapid and major reorganization of the North Atlantic's surface hydrography to explain changes in IRD flux independently of ice sheet calving dynamics.